2017
DOI: 10.1038/cddiscovery.2016.97
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells in alleviating sepsis-induced mice cardiac dysfunction via inhibition of mTORC1-p70S6K signal pathway

Abstract: Sepsis-induced cardiac dysfunction remains a major cause of morbidity and mortality in patients suffered from severe trauma. Mesenchymal stem cells (MSCs) -based treatment has been verified as a promising approach to mitigate the sepsis-induced cardiac dysfunction, but the mechanism is still ambiguous. Thus, our study was designed to explore the potential role of MSCs in sepsis-induced cardiac dysfunction. In vivo bioluminescence imaging revealed 80% acute donor cell death of bone marrow-derived MSCs (BM-MSCs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Previous studies have also shown modulation of SIRS phase of sepsis and sepsis-induced mortality by bone marrow transplant (Lorigados et al, 2018, Huang et al, 2017. We hypothesized that ABCF1 deficiency in bone-marrow-derived haemopoietic cells was responsible for this increase in susceptibility to developing sepsis.…”
Section: Abcf1 Targets Traf3 For K63-polyubiquitination and Controls mentioning
confidence: 88%
“…Previous studies have also shown modulation of SIRS phase of sepsis and sepsis-induced mortality by bone marrow transplant (Lorigados et al, 2018, Huang et al, 2017. We hypothesized that ABCF1 deficiency in bone-marrow-derived haemopoietic cells was responsible for this increase in susceptibility to developing sepsis.…”
Section: Abcf1 Targets Traf3 For K63-polyubiquitination and Controls mentioning
confidence: 88%
“…Minicircle vectors were used to transfect CMs in accordance with the manufacturer's instructions (System Biosciences, CA, USA). Adenovirus vectors for MT2 silencing and MT2 overexpression as well as control lacZ vector were commercially purchased from GeneChem Co., Ltd (Shanghai, China) and transfected as we previously described . To inhibit Notch1 expression, cells were transfected with small interfering RNA against Notch1 conjugated with Lipofectamine 3000 for 6 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Adenovirus vectors for MT2 silencing and MT2 overexpression as well as control lacZ vector were commercially purchased from GeneChem Co., Ltd (Shanghai, China) and transfected as we previously described. 36 To inhibit Notch1 expression, cells were transfected with small interfering RNA against Notch1 conjugated with Lipofectamine 3000 for 6 hours. All the siRNA agents were purchased from Santa Cruz (Santa Cruz, Dallas, TX, USA).…”
Section: Cell Transfectionmentioning
confidence: 99%
“…route. 15,20,27,28 Interestingly, in animal models of hematological conditions, the effectiveness of MSC therapy was comparable or superior after i.p. compared with i.v.…”
Section: New Insights Into the Localization Survival And Migratory mentioning
confidence: 99%
“…), subcutaneous, and intramuscular injections. [15][16][17][18][19][20][21] In one such study, i.v.-administered adipose-derived MSCs (both live and heat-inactivated) were found not to migrate to an inflammatory site, with most remaining localized to the lungs. 21 Similar findings were made using postmortem quantification of an MSC-delivered radioactive isotope to investigate the distribution of i.v.-administered MSCs to individual tissue including the kidneys.…”
Section: New Insights Into the Localization Survival And Migratory mentioning
confidence: 99%